Molecular characterization of extended-spectrum beta lactamase (ESBL) producing klebsiella pneumoniae and escherichia coli among hospitalized patients in Oman - Mourad, Lobna (AUC Knowledge Fountain, 2011)
Hospital-acquired infections due to ESBL-producing gram-negative rods are a worldwide healthcare problem causing substantial patient morbidity and mortality. In the Middle East, a significant increase in incidence and prevalence has been reported recently due to the misuse of antibiotics and lack of coherent antimicrobial resistance (AR) surveillance programs. The aim of the study was to determine the level of genotypic diversity and mechanism of AR of E. coli and K. pneumoniae ESBL-producing isolates from nosocomial infections among patients in Oman. 35 E. coli and 14 K. pneumoniae isolates were used in the study. Antibiotic susceptibility testing (AST) and ESBL screening was conducted via disk diffusion and E-test following CLSI (Clinical and Laboratory Standards Institute) guidelines. ESBL producers were screened for blaCTX-M, blaSHV, blaOXA, and blaTEM resistance markers via PCR. All PCR amplicons were sequenced to determine their allelic variants. In order to demonstrate overall genotypic diversity, Pulsed-Field Gel Electrophoresis (PFGE) analyses were done separately for all E. coli and K. pneumoniae isolates. 40 (80%) isolates were determined to be ESBL producing bacteria (27 E. coli and 13 K. pneumoniae). The highest level of AR (>70%) was against tetracycline, ampicillin, nalidixic acid, cephalothin, and cefpodoxime. The lowest level of AR was against chloramphenicol, amikacin and ticarcillin-clavulanic acid. Resistance against imipenem was not detected. Similarity of K. pneumoniae isolates ranged from 61% to 100%. Three K. pneumoniae clusters (n= 7; 58%) had â ¥ 80% similarity suggesting high level of similarity. E. coli PFGE analyses showed an overall similarity of 64% with 4 clusters (n= 14; 54%) showing 80% similarity. No correlation was demonstrated between the AR pattern and genotypic similarity for either species. Percentages of isolates with genetic markers for blaCTX-M, blaSHV, blaTEM, and blaOXA were 73%, 24%, 68%, and 60% respectively. DNA sequencing analyses revealed that the most common AR mechanism in these ESBL isolates is due to blaCTX-M-15 marker. In addition, SHV-1, SHV-11, SHV-12, TEM-1, and OXA-1 contribute to the overall AR mechanisms in nosocomial ESBL isolates from Oman. This is the first study characterizing the AR mechanism of ESBL's isolates from hospital-acquired infections in Oman. The results showed that hospital-acquired E. coli isolates from Oman are more diverse than K. pneumoniae. The blaCTX-M-15 is the most abundant mechanism conferring ESBL phenotype on E. coli and K. pneumoniae, while the ESBL-SHV-type was the least abundant.